Ethnic Discrimination and the Migration of Skilled Labor - Frédéric Docquier; Hillel Rapoport (Bar-Ilan University, Department of Economics, 2001)
We consider a small open developing economy, whose population is bifurcated into a majority and a minority group, the latter lacking political influence. Agents are heterogeneous in skills, and decide whether to invest in education when young and whether to migrate in their adulthood. Assuming a rent-extraction basis for discrimination, we first endogenize ethnic discrimination in the benchmark case of an economy closed to migration, and then explore how migration prospects affect ethnic inequality. Under the free migration assumption, we find the intuitive result that migration prospects have a protective effect on the minority. Moreover, the optimal discrimination rate (from the majority's perspective) is shown to be such that there is no migration at equilibrium, unless the distribution of individuals' skills exhibits marked asymmetries. Last, we find that immigration restrictions set by receiving countries have the paradoxical effect of creating migration flows which would otherwise have remained latent.
Keywords: F22; J15; J24; J71; O15; 330; Ethnic minorities; discrimination; migration; human capital formation